The Impact of Students Dropout on Human Development in Iraq For Period ( 2001 ــ 2011 ) - فرحان اسيا كاظم; رضا عبد الناصر قادر (Journal of Economics and Administrative Sciences, 2013)
Abstraet Students dropout from the Education has a negative phenomena on individual and society and even on different aspects of life especially on the economic aspect , Thus our research tries studying and analyzing the relation between the size of dropout and human development level in Iraq and as (research sample) the first decade of this century as a studying period, the study includes the dropout in Secondary schools and depending the formal records as a main source to evaluate the size of this problem in Iraq , which shows an increase in the size of dropout in this period in comparison with the last decades of the twentieth century, this produces a negative effect on human development, specially education, health and living standards. when we take the relation between the dropout development and which have impact on the othier which shows a mutual impact, that produces a difficulty of the problem to diagnose and give remedy, the diagnosing of the problem is the task of the researcher , but remedy is the task of society . This needs a central plan to deal with the causes of this problem , and the matter of fact , it is avery dangerous task , as Ministry of Education cannot deal with it alone to minimize this phenomena , but the government can , and to find the proper Solution within a central plan responsible and supervising .